2024
DOI: 10.3847/1538-4357/ad47b6
|View full text |Cite
|
Sign up to set email alerts
|

Binding Energies of N-bearing Species on Interstellar Water Ice Mantles by Quantum Chemical Calculations

Berta Martínez-Bachs,
Stefano Ferrero,
Cecilia Ceccarelli
et al.

Abstract: Of the about 300 gas-phase molecular species so far detected in the interstellar medium (ISM), mostly via observations of their rotational lines, around 40% contain nitrogen (N) atoms. Likewise, of the less than a dozen interstellar molecules, firmly or likely detected in the solid-state water-dominated icy matrix by means of infrared observations, two bear N. A crucial parameter that regulates whether a species is in the gas or adsorbed on the icy phase is their binding energy (BE) toward the icy grain. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
1
0
0
Order By: Relevance
“…The distribution is bimodal, representing both hydrogen bonding and hemibonding. With 85% the latter dominates the distribution with a mean binding energy value of 48.6 kJ mol –1 , extending from 27.0 to 74.7 kJ mol –1 , closely aligning with recent results by Martinez-Bachs et al, which report a binding energy range of 21.7 to 64.8 kJ mol –1 , and the work by Rimola et al, who observed a binding energy of 76.6 kJ mol –1 in a cavity-like structure of a 33-water-molecule cluster, characterized by a high number of intermolecular interactions. This value is compatible with the high end of our distribution and the difference is likely to be produced by the different theory level, where the density functional BHandHLYP was used in combination with a double-ζ basis set for geometries and zero point energies and a triple-ζ one for energy refinement.…”
supporting
confidence: 90%
“…The distribution is bimodal, representing both hydrogen bonding and hemibonding. With 85% the latter dominates the distribution with a mean binding energy value of 48.6 kJ mol –1 , extending from 27.0 to 74.7 kJ mol –1 , closely aligning with recent results by Martinez-Bachs et al, which report a binding energy range of 21.7 to 64.8 kJ mol –1 , and the work by Rimola et al, who observed a binding energy of 76.6 kJ mol –1 in a cavity-like structure of a 33-water-molecule cluster, characterized by a high number of intermolecular interactions. This value is compatible with the high end of our distribution and the difference is likely to be produced by the different theory level, where the density functional BHandHLYP was used in combination with a double-ζ basis set for geometries and zero point energies and a triple-ζ one for energy refinement.…”
supporting
confidence: 90%